2013
DOI: 10.1016/j.ins.2013.02.030
|View full text |Cite
|
Sign up to set email alerts
|

A time series forest for classification and feature extraction

Abstract: A tree-ensemble method, referred to as time series forest (TSF), is proposed for time series classification. TSF employs a combination of entropy gain and a distance measure, referred to as the Entrance (entropy and distance) gain, for evaluating the splits. Experimental studies show that the Entrance gain improves the accuracy of TSF. TSF randomly samples features at each tree node and has computational complexity linear in the length of time series, and can be built using parallel computing techniques. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
254
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 488 publications
(281 citation statements)
references
References 22 publications
0
254
0
3
Order By: Relevance
“…However, in [11] it was shown that there is little difference between the most cited measures in the literature. The majority of recent work proposing alternative classifiers [23,10,7] tends to embed any transforms within the classification process, thus making it hard to qualitatively or quantitatively assess which element of the proposed technique is the source of any improvement in accuracy. We separate the process of representation and the classifier in the hope of more transparency.…”
Section: Data Transformationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in [11] it was shown that there is little difference between the most cited measures in the literature. The majority of recent work proposing alternative classifiers [23,10,7] tends to embed any transforms within the classification process, thus making it hard to qualitatively or quantitatively assess which element of the proposed technique is the source of any improvement in accuracy. We separate the process of representation and the classifier in the hope of more transparency.…”
Section: Data Transformationsmentioning
confidence: 99%
“…Ensembles have been used in time series data mining [7,23,10]. Deng and Runger [10] propose a random forest [5] built on summary statistics (mean, slope and variance) of subseries.…”
Section: 22mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the evidence in favour of 1-NN classifiers with Euclidean or Dynamic Time Warping (DTW) distance, there has been a spate of recent research proposing alternative approaches. These include shapelets [13,20,19], weighted dynamic time warping [10], support vector machines built on variable intervals [16], tree based ensembles constructed on summary statistics [6], fusion of alternative distance measures [2], and transform-based ensembles [1]. We consider the shapelet approach one of the most promising of these new methods.…”
Section: Introductionmentioning
confidence: 99%
“…These continuous attributes are recorded as discrete signals by means of digital systems. In the last decade particularly, many studies have focused on the discretization of already discrete signals for the discovery of knowledge [9][10][11][12][13][14][15]. There are two parameters that affect results in discretization: the number of cut points and their locations.…”
Section: Introductionmentioning
confidence: 99%